A Retrospective Evaluation of Pregnancy Outcomes Following Bariatric Surgery: A Single-Center Experience - Wang X; Liu J; He A; Dong Z; Chen X; Yu S; Gao L; Wang H; Chen W; Hu R; Jiang S; Wang J; et al. (Diabetes, Metabolic Syndrome and Obesity, 2022)
Xiufang Wang,1,* Jia Liu,1,* Andong He,1 Zhiyong Dong,2– 4 Xiaomei Chen,2– 4 Shuqing Yu,2– 4 Lilian Gao,2– 4 Huaxi Wang,2– 4 Wenhui Chen,2– 4 Ruixiang Hu,2– 4 Shuwen Jiang,2– 4 Jianxue Wang,2– 4 Yuan Chen,2– 4 Cunchuan Wang,2– 4 Wah Yang,2– 4 Ruiman Li1 1Department of Obstetrics and Gynecology, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 2Department of Metabolic and Bariatric Surgery, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 3Jinan University Institute of Obesity and Metabolic Disorders, Guangzhou, People’s Republic of China; 4Guangdong-Hong Kong-Macao Joint University Laboratory of Metabolic and Molecular Medicine, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruiman Li, Department of Obstetrics and Gynecology, The First Affiliated Hospital of Jinan University, No. 613, Huangpu Avenue West, Guangzhou, People’s Republic of China, Email hqyyck@126.com Wah Yang, Department of Metabolic and Bariatric Surgery, The First Affiliated Hospital of Jinan University, No. 613, Huangpu Avenue West, Guangzhou, People’s Republic of China, Email yangwah@qq.com; yangwah@connect.hku.hkBackground: Bariatric and metabolic surgery (BMS) is an effective treatment for obesity and its complications, but its effect on pregnancy outcomes is inconclusive. The present study aimed to investigate women’s pregnancy status and outcomes as well as the impact of pregnancy intervals after BMS.Methods: The menstrual cycle and fertility status of women who underwent BMS in our centre between July 2010 and January 2021 were retrospectively analyzed and followed up until one-year post-delivery. The pregnancy outcomes after BMS were observed, including changes in weight, pregnancy interval, pregnancy complications, weight and health status of the newborn (premature birth, admission to neonatology, or deformity).Results: We identified 31 women who were successfully conceived after BMS. There were statistical differences in weight and menstrual status before and post-operation (P < 0.05), and 77.97% of them had remission or recovery of obesity-related comorbidities. Eighteen patients delivered successfully after BMS, but there were still 12 cases of spontaneous abortion and 1 case of induced abortion. The abortion rate in pregnancy intervals less than 2 years was higher than those ≥ 2 years (P = 0.045). Of the women who delivered successfully, 5 had pregnancy-specific complications, including gestational diabetes mellitus and hypertensive disorder of pregnancy. However, the growth and development of the newborn are normal since the birth follow-up.Conclusion: The present results suggest that the abortion rate in pregnancy intervals less than 2 years was higher than those ≥ 2 years. It is recommended that postoperative patients avoid pregnancy until their weight is stable to reduce the risk of adverse pregnancy outcomes.Keywords: pregnancy, bariatric surgery, metabolic surgery, obesity